Academic Salaries in Western Europe - Jongbloed, Ben (International Higher Education, 2012)
In its recent (2011) communication "Supporting Growth and Jobsan agenda for the Modernisation of Europe's Higher Education Systems," the European Commission has once again urged Europe's universities to reform their human-resources policiesto increase the autonomy of the universities in this respect and to introduce incentives to re- ward excellence in teaching and research. Europe's universities will need to recruit academics by flexible, open, and transparent procedures and to provide them with attractive career prospects. Without a committed and adequately compensated professoriate, universities will find it hard to recruit the best and brightest academic talent to work for them and to provide the teaching and research that Europe needs, in order to be a competitive knowledge-driven region.